Pelatihan Proses Milling Bagi Mahasiswa di Growth Centre LLDIKTI Wilayah - I - Jufrizal, Jufrizal; Hermanto, Tino; Riadi, Selamat; Marwan, Marwan (CV. IRA PUBLISHING, 2023)
The milling process is one of the essential techniques in the manufacturing industry used to produce components using milling machines. For engineering or manufacturing science students, understanding the milling process is relevant and valuable. The milling process is commonly used in various industrial sectors, including automotive, aircraft, energy, etc. Understanding the basic principles and techniques of the milling process will provide a solid foundation for students to develop careers in these various industries. The milling process involves the use of a milling machine. Students skilled in operating these machines will have a competitive advantage in the world of work. They will be able to contribute to product development, tool design, and efficient manufacturing processes. Students will learn how to read and understand technical drawings, choose the right cutting tools, as well as workpiece measurement techniques prior to the milling process. This capability will broaden their understanding of product engineering and design. The results of the training showed that almost all students were able to perform basic techniques in the milling process, as evidenced by their ability to produce products according to the technical drawings provided.